2020
DOI: 10.3390/ma13194345
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Steel-Reinforced Green Concrete Containing Recycled Coarse Aggregate Additions in Sulfate Media

Abstract: Novel green concrete (GC) admixtures containing 50% and 100% recycled coarse aggregate (RCA) were manufactured according to the ACI 211.1 standard. The GC samples were reinforced with AISI 1080 carbon steel and AISI 304 stainless steel. Concrete samples were exposed to 3.5 wt.% Na2SO4 and control (DI-water) solutions. Electrochemical testing was assessed by corrosion potential (Ecorr) according to the ASTM C-876-15 standard and a linear polarization resistance (LPR) technique following ASTM G59-14. The compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…Another strategy is the utilization of waste materials such as glass [ 23 ], PET bottles or containers [ 24 ], ceramic tiles and coverings, ceramic sanitary products [ 25 ], ceramic clay bricks [ 26 ], tyres and rubber [ 27 ], concrete residues [ 28 ], agricultural wastes [ 29 , 30 ], metallurgy slags [ 31 , 32 , 33 ], industrial wastes [ 34 , 35 , 36 ], or coconut husks [ 37 ]. All these additions proportionate a positive environmental impact due to the reutilization of materials and products which had completed their service life.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy is the utilization of waste materials such as glass [ 23 ], PET bottles or containers [ 24 ], ceramic tiles and coverings, ceramic sanitary products [ 25 ], ceramic clay bricks [ 26 ], tyres and rubber [ 27 ], concrete residues [ 28 ], agricultural wastes [ 29 , 30 ], metallurgy slags [ 31 , 32 , 33 ], industrial wastes [ 34 , 35 , 36 ], or coconut husks [ 37 ]. All these additions proportionate a positive environmental impact due to the reutilization of materials and products which had completed their service life.…”
Section: Introductionmentioning
confidence: 99%
“…The defense mechanism in the case of sulfate salt penetration into the concrete is mainly based on the buffering effect of the binder components that maintain the alkaline environment of the concrete. The migration of sulfate ions with significant concentration into the concrete structure poses a risk of the formation of corrosive chemicals, in particular: ettringite (C 3 A•3CaSO 4 •32H 2 O) and gypsum (CaSO 4 •2H 2 O), as indicated by the authors [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, they have tried to find solutions that delay or reduce the emissions of CO 2 produced by the cement industry in the world. In the present research, Sugar Cane Bagasse Ash (SCBA) and Silica Fume (SF) were used as alternative materials to Portland Cement due to their pozzolanic characteristics [7][8], in addition It is known that one of the major problems of the integrity of reinforced concrete structures is the corrosion of steel [9][10][11][12][13][14], but it has been reported that the use of this type of pozzolanic materials increases the corrosion resistance of concrete reinforcing steel exposed to aggressive media such as sulfate and chloride ions and contribute to a reduction in CO 2 emissions, concrete that are considered sustainable, ecological or green [15][16][17][18][19][20]. Four concrete mixes were designed in accordance with ACI 211.1, the first being 100% CPC and the remaining three were made with partial substitutions in percentages of 10%, 20% and 30% of the CPC by combinations of CBCA and HS After its performance, they were placed in two different media, control medium (drinking water) and a 3.5% MgSO 4 solution, and tests of F´c and Modulus of elasticity performed at 7, 14 and 28 days.…”
Section: Introductionmentioning
confidence: 99%